Significance of duck in the transmission of avian influenza virus (University Journal of Zoology, Rajshahi University, 2012)
DOI: http://dx.doi.org/10.3329/ujzru.v30i0.10759Univ. j. zool. Rajshahi Univ. Vol. 30, 2011 pp.77-79